INCREASING VOCABULARIES TO SUPPORT LANGUAGE SKILLS BY FIFTH SEMESTER STUDENTS OF AKRB YOGYAKARTA - Marita Nurharjanti (Universitas Sarjanawiyata Tamansiswa, 2021)
This research was to figure out the students’ ways of increasing vocabularies to support language skills of fifth semester students of Radya Binatama Broadcasting Academy Yogyakarta. Class activities were insufficient for each student to learn maximally. This hindrance made some students to be more creative in learning vocabularies to support their language skills of English. The study was categorized as descriptive qualitative research. The writer used documentation, observation, in-depth interview, data triangulation and open-questionnaire methods. To analyze the data, the writer used constant comparative study. The results were as follows: first, the students increased vocabularies through listening from news and interview programs on TV and radio, music and films from their private collections such as CD, DVD, cassette or learning from the family member. Second, they increased vocabularies through reading from text, book, novel, newspaper and film/ song text. Third, they increased vocabularies through speaking by oral repeating from song and film, taking part in debating activities or competitions, making conversation in working place or in the organization, and delivering speech. Fourth, they developed vocabularies from writing via emails, composing story, writing articles and diary. Fifth, in translation, they used both internet because of the time efficiency and also dictionary. Keywords: increasing vocabularies, students, language skills